Emotional Intelligence Effect and Side of Gender Spritual Intelligence against Performance of Employees in the West Sumatra Staffing Parliament - Yusnaena Yusnaena; Alpha Perdana (DeReMa (Development Research of Management): Jurnal Manajemen, 2015)
Human resources play an important role in the organization of the company. Although supported by the infrastructure and sufficient financial resources, without the support of human resources who are competent in their respective fields of activities in the organization, the company will not run properly. It is proved that human resources are the key issue and have to be managed as well as possible, because as the key, human resources will determine the success of an organization's operational activities. Provincial Parliament stressed the need for employees who have emotional and spiritual balance accumulated in the form of morality working and able to work together in solid team work. It is necessary for emotional intelligence and spiritual intelligence. But the phenomenon in the field indicates the employee's performance is far from the desired expectation as there are many employees who are less concerned about jobs, less concerned about the peer delay - temporize absence of a sense of community work, is selfishness and want to win yourself all this illustrates the field of emotional intelligence oversight and intelligence spiritual so disturbing to the achievement of actual performance. This study is a descriptive study that compares the explanatory theories with circumstances that occur in the field. The sampling method selected is a total sampling technique. Data was processed using a multiple linear regression analysis formula. The results of this study conclude that the variables Emotional Intelligence have significant positive effect on employee performance in the Secretariat of the West Sumatra Provincial Parliament. The variable Spiritual Intelligence does not significantly influence the performance of employees of the West Sumatra Provincial Parliament Secretariat.